Comparison of three nutritional screening tools for detecting sarcopenia in patients with maintenance hemodialysis - Chen, Xiaoyu; Han, Peipei; Zhu, Xiaoyan; Song, Peiyu; Zhao, Yinjiao; Zhang, Hui; Yu, Chen; Niu, Jianying; Ding, Wei; Zhao, Junli; Zhang, Liming; Qi, Hualin; et al. (Frontiers in Public Health, 2022)
Background Malnutrition, dynapenia, and sarcopenia are prevalent conditions among patients with maintenance hemodialysis (MHD). They are related to numerous adverse health outcomes. The aim of this study was to compare the effect of three nutritional screening tools on predicting the risk of dynapenia and sarcopenia in patients with MHD. Methods From July 2020 to April 2021, a total of 849 patients with MHD were enrolled at seven different healthcare facilities in Shanghai, China in this multi-center cross-sectional study. Geriatric nutritional risk index (GNRI), malnutrition inflammation score (MIS), and creatinine (Cr) index were used for nutritional assessment. The cutoff values of muscle mass and strength to define dynapenia, pre-sarcopenia, and sarcopenia were based on the consensus by the Asia Working Group of Sarcopenia in 2019. Results Among 849, almost 60% were malnourished with the majority suffering from dynapenia (27.7%), followed by sarcopenia (22.7%), and pre-sarcopenia (6.2%).The area under the receiver–operating characteristic curve for GNRI was 0.722 [95% confidence interval (CI) = 0.684–0.760] and 0.723 (95% CI = 0.663–0.783) in predicting sarcopenia and pre-sarcopenia. The GNRI [odds ratio (OR) =6.28, 95% CI: 4.05–9.73], MIS (OR =1.91, 95% CI: 1.31–2.78), and the Cr index (OR =2.73, 95% CI: 1.71–4.34) were all significantly associated with the risk of sarcopenia. More importantly, the sarcopenia predictability of the GNRI appears greater than the MIS and Cr index, while MIS was similar to the Cr index. Similarly, the superiority of GNRI prediction was also found in pre-sarcopenia, but not in dynapenia. Conclusion All the three nutritional screening tools were significantly associated with an increased risk of sarcopenia. The sarcopenia predictability of the GNRI was greater than the MIS and Cr index.